Moral and political philosophy : key issues, concepts and theories - Smith, Paul, 1953- (Basingstoke [England] ; New York : Palgrave Macmillan, 2008)
This text provides a comprehensive examination of key concepts and theories in moral and political philosophy. With a clear focus on the essentials of each topic, Smith presupposes no prior knowledge and relates moral philosophy to social and political issues.
Drug laws -- Justifications of punishment -- Civil disobedience : is there a duty to obey the law? -- Global poverty -- Liberty -- Liberty-limiting principles -- Rights -- Equality and social justice -- Moral relativism -- Utilitarianism -- Kantian moral philosophy -- John Rawls's theory of justice.
Includes bibliographical references (p. 215-250) and index.
Keywords: Law and ethics; Political ethics; Ethics; Political science -- Philosophy; Social ethics